(untitled) (International Journal of Innovative Research in Computer Science & Technology, 2022)
This article focuses on Einstein’s theory of relativity and Minkowski space-time, which combines three dimensions of space and a fourth dimension of time. It contrasts and examines the evolution of time travel in science fiction and science. The wormhole hypothesis and the Tipler cylinder are among the time travel hypotheses investigated, as is the possibility of human time travel. This research investigates time as a fourth dimension, as well as curved space-time, both of which are often overlooked. The paucity of information about time was one of my major realizations throughout my studies, and I liked investigating time as a social construct. Given how seldom we ponder the effects of actions in our everyday lives, the amount of hurdles to successful time travel was especially apparent. Time travel was hampered by paradoxes, such as the grandfather paradox, but I discovered techniques to solve them throughout my studies. I also considered the societal and economic implications of time travel, knowing that the risks are numerous and could encourage corruption in our cultures. Entropy